(3GJNGP GdbQGQGJ GdJfXjejIs - (3eMeO YHO GdaJGM(B, (3jGZjs ((3YeGf(B:s (3OGQ hGFd(B,s, 2010)
(3GdJYQja HGJNGP GdbQGQGJ GdJfXjejI , JWhQ GdacQ GdGOGQj aj ehVhY GJNGP GdbQGQGJ GdJfXjejI , fehPL GJNGP GdbQGQGJ GdGOGQjI , NWhGJ GdGSdhH GdYdej dGJNGP GdbQGQGJ GdJfXjejI (B( (3eQGMd YedjI GJNGP GdbQGQGJ GdJfXjejI (B) (3, OhQ GdeYdheGJ aj GJNGP GdbQGQGJ GdJfXjejI , OhQ GdGJUGd GdGOGQj aj JHGOd GdeYdheGJ GdOGNdI h GdNGQLI ef GdJfXje h cjajI JMSjfgG , cjajI JMSjf YedjI GJNGP GdbQGQGJ GdJfXjejI (B( (3JbQjQ Mhd GdGFJeGQ HGdbQGQGJ GdeDefI (B)s
(3eQGLY (B: (3dcd aUd eQLYs
Keywords: (3GJNGP GdbQGQGJs; (3GOGQI GdGYeGds; (3GdGOGQIs